ADVANCING INSTRUCTIONAL METHODOLOGIES IN HIGHER EDUCATION VIA INFORMATION AND COMMUNICATION TECHNOLOGIES - Ismatov Dilmurod Elmurodovich (Western European Studies, 2026)
The paper explores the benefits of applying information and communication technologies in subject instruction, such as fostering students’ knowledge and competencies, increasing instructional efficiency, personalizing training activities, and strengthening student motivation.
Keywords: information and communication technologies; didactic system; multimedia